Methods for assessing the condition of the nasal cavity and paranasal sinuses in the phased conservative treatment of rhinosinusitis patients with drugs of plant origin - Yu. V. Nazarochkin; O. V. Nazarochkina (Лечащий Врач, 2021)
The article presents the data of the analysis of clinical and instrumental researches in the publications of the results of the use of triterpene glycosides — lyophilized cyclamen extract — in the treatment of patients with rhinosinusitis, cited in PubMed and Cochrane Library. Most of the works contain data of observations, systematized by visual-analog scales, allowing to consider this therapy an effective adjunct treatment of rhinosinusitis, contributing to the adaptation of the nasal mucosa and application of standard therapy.